Resistance to pyrethroids in the maize weevil, Sitophilus zeamais - Cash, Francesca (2012)
The maize weevil is a pest of stored crop products, predominantly maize across humid areas of the world. The Sitophilus zeamais were controlled with pyrethroids until resistance emerged in areas across Brazil. This resistance was found to be conveyed by a super-kdr mutation in the voltage gated sodium channel (VGSC). A change from threonine to isoleucine at the 929 position in domain II, segment 5 of the VGSC was found to be the cause of resistance. This mutation also conveyed cross resistance to DDT. The project aimed to assess the level of resistance conveyed by the T929I mutation in lab populations of the maize weevil, to test for the presence of this mutation in the field, and finally to assess mutations at the T929 site using electrophysiology.